2020
DOI: 10.3389/fbioe.2020.00764
|View full text |Cite
|
Sign up to set email alerts
|

An in situ Gelling System Based on Methylcellulose and Tranilast Solid Nanoparticles Enhances Ocular Residence Time and Drug Absorption Into the Cornea and Conjunctiva

Abstract: We previously developed ophthalmic formulations containing tranilast nanopartaicles (ophthalmic TL-NPs formulations), and found them to show high uptake into ocular tissues. In this study, we aimed to design an in situ gel incorporating TL-NPs with 0.5-3% methylcellulose (MC, type SM-4) to ensure long residence time of the drug at the ocular surface. The ophthalmic TL-NPs formulations were prepared by the bead mill method, which yielded a mean particle size of˜93 nm with or without MC (0.5-3%). Although the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 36 publications
0
39
0
Order By: Relevance
“…Moreover, various drug delivery systems, such as microparticles, nanoparticles, nanostructured lipid carriers, nanosuspensions, nanocrystals, liposomes, and dendrimers have been studied to overcome issues relating to the absorption, retention, and stability of drugs [ 13 , 14 , 15 ]. In previous research, we also designed disulfiram and indomethacin nanoparticles using the bead mill, and showed that the adsorption to the surface of cyclodextrin decreases the cohesion of nanoparticulate solids, and the addition of 2-hydroxypropyl-β-cyclodextrin (HPCD) was suitable for the preparation of nanoparticles using mill methods [ 16 , 17 ]. Furthermore, we found that energy-dependent endocytosis was related to the transcorneal penetration of ophthalmic formulations containing nanoparticles [ 16 , 18 ], and the instillation of ophthalmic formulations containing nanoparticles can deliver the drug into the lens [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, various drug delivery systems, such as microparticles, nanoparticles, nanostructured lipid carriers, nanosuspensions, nanocrystals, liposomes, and dendrimers have been studied to overcome issues relating to the absorption, retention, and stability of drugs [ 13 , 14 , 15 ]. In previous research, we also designed disulfiram and indomethacin nanoparticles using the bead mill, and showed that the adsorption to the surface of cyclodextrin decreases the cohesion of nanoparticulate solids, and the addition of 2-hydroxypropyl-β-cyclodextrin (HPCD) was suitable for the preparation of nanoparticles using mill methods [ 16 , 17 ]. Furthermore, we found that energy-dependent endocytosis was related to the transcorneal penetration of ophthalmic formulations containing nanoparticles [ 16 , 18 ], and the instillation of ophthalmic formulations containing nanoparticles can deliver the drug into the lens [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…MC is frequently used as a gelling agent in the ophthalmic field [ 34 ], and the proposed in situ gelling system based on MC shows promise for sustained ocular drug delivery. We also presented a combination of the in situ gelling system and tranilast nanoparticles and reported that the concentration of MC used in the in situ gelling system has an optimum value and that the release of nanoparticles is suppressed when a high MC (3%) concentration is used [ 26 ]. Based on these results, in this study, we used MC to prepare the Dis-NPs/ISG and determined the optimal MC content in the Dis-NPs/ISG to be 1.5%.…”
Section: Discussionmentioning
confidence: 99%
“…In order to further increase the ocular bioavailability ( BA ), we attempted to combine nanoparticles and an in situ gelling system. We also reported that a combination of nanoparticles and an in situ gelling system using methylcellulose (MC) increased the ocular BA [ 26 , 27 ]. These high ocular BA s may enable drug delivery to the retina.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of the ophthalmic IMC-NC formulations were measured following our previous reports [ 20 , 21 , 22 , 23 ]. Briefly, each ophthalmic IMC-NC formulation was stored in the dark at 20 °C for 30 days to measure IMC dispersibility, and samples were taken from 5 mm under the surface over time.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we showed that the nanoparticles of IMC induced the multiple energy-dependent endocytosis in the cornea, and caveolae-dependent endocytosis (CME), clathrin-dependent endocytosis (CME), and micropinocytosis (MP) enhanced ocular absorption of IMC from ocular dosage forms [ 21 ]. Moreover, we reported that the 1.5% methylcellulose (MC) in situ gelling system was gelled after the instillation, and enhanced contact time with the ocular surface of NCs, resulting in improving the ocular BA [ 22 , 23 ]. Thus, in situ gel (ISG)-incorporating NCs may achieve high ocular drug BA by avoiding rapid precorneal clearance.…”
Section: Introductionmentioning
confidence: 99%